Pendampingan Pengembangan Lembar Kerja Peserta Didik (LKPD) Matematika Berbasis Model Kolaboratif dengan Pendekatan PMR - Tali Wangge, Maria Carmelita; Bela, Maria Editha; Wewe, Melkior; Bhoke, Wilibaldus; Ndao, Yosefa Vilmit; Kapoh, Jeane Rosalia; Lujur, Veronika; Rema, Iventius Bai; Megu, Bonifasius (Abdimas Indonesian Journal, 2025)
The collaborative model-based development of Student Worksheets (LKPD) for Mathematics using the Realistic Mathematics Education (RME) approach aims to improve teachers' ability to design LKPD that are contextual and meaningful, and encourage active student collaboration. This mentoring program is implemented through several stages: identifying teacher needs, training in developing RMR-based LKPD, mentoring in the design and testing process, and reflecting on implementation results. The methods used in this activity include workshops, group discussions, observations, and evaluation of teacher work. The mentoring program results indicate that teachers gained an increased understanding of PMR principles and improved their ability to develop LKPD that emphasize active student involvement in real-world problem-solving through group collaboration. Furthermore, the resulting LKPD were deemed valid and suitable for use based on expert assessment and positive student feedback. Thus, this mentoring program contributes to improving the quality of mathematics learning materials in schools and supports the implementation of more innovative, collaborative, and contextual learning.